The Muslim Researcher Reflections on Insider/ Outsider Research in Indonesia (Peniliti Muslim Refleksi Penilitian Insider dan Outsider di Indonesia) - Seise, Claudia (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
The article takes up the topic of religious insider and outsider research and looks especially at the issue of advantages and disadvantages of being a religious insider doing qualitative research in religious communities similar to one’s own. As a case study serves my personal experience of being a convert Muslim woman doing research among Islamic communities in Indonesia. During research, I came to understand that the plurality of different Islamic practices found in Indonesia makes it difficult to become a ’true’ and ‘complete‘ insider to this variety of Islamic teachings and practices. My main argument is that, at least in the Indonesian context, it is impossible to be a complete religious insider to each aspect of the plurality of Islamic practices despite being an insider to Islam, a Muslim. This in turn leads me to discuss advantages and disadvanatges of being a religious insider. Keywords: Muslim Researcher, Research Methodology, Research in Indonesia, Qualitative Research, Southeast Asia, Islam. Abstrak Artikel ini membicarakan tema tentang peniliti insider atau outsider dengan fokus peniliti yang beragama. Artikel ini khususnya menganalisiskan manfaat dan mudarat menjadi seorang insider yang mempunyai agama yang sama dengan orang yang ditiliti. Sebagai contoh saya memandang kasus personil saya sendiri sebagai peniliti Muslim mualaf yang melakukan penilitian diantara komunitas-komunitas Muslim di Indonesia. Melalui penilitian saya, saya memahami bahwa pluralitas praktek orang Muslim di Indonesia membuat sulit untuk menjadi seorang insider yang sebenarnya untuk semua keanekaragaman pemahaman Islam yang ada di Indonesia. Argumen utama saya adalah bahwa dalam kontex Indonesia, tidak mungkin untuk menjadi insider religi yang sebenarnya untuk seluruh aspek-aspek pluralitas Islam. Walaupun menjadi seorang Muslim sekalipun. Pemahaman tersebut membawa saya untuk membicarakan manfaat dan mudarat menjadi seorang insider agama. Kata Kunci: Peniliti Muslim, Metodologi Penilitian, Penilitian di Indonesia, Qualitative Research, Asia Tenggara, Islam.